A brand new two-phase wet oxidation absorption system for the simultaneous removal of SO2 and NOX from simulated marine exhaust gas. (November 2022) - Zhao, Junxiong; Wei, Qifeng; Bi, Dongkui; Liu, Lijuan; Wang, Shanshan; Ren, Xiulian
Abstract: Marine engine exhaust emissions are increasingly harmful to the natural environment and human health and must be controlled. A self-synthesized amide (BAD, C12 H25 NO) in the laboratory shows a strong absorption capacity of nitric acid and nitrous acid, which may solve the problem that only using chlorine-based oxidant as an absorbent cannot completely absorb or retain NO2 produced by NO oxidation in previous studies. Based on Multiwfn and VMD (Visual Molecular Dynamics) program calculation, the formation mechanism of hydrogen bonds between BAD with nitric acid and nitrous acid was revealed by electrostatic potential (ESP) analysis and further confirmed by FT-IR (Fourier transform infrared spectroscopy) spectra research. Subsequently, simultaneous removal of SO2 and NOX from simulated flue gas was carried out by using NaClO/BAD as a two-phase composite absorbent, and the maximum removal efficiencies of SO2 and NOX were 98.9% and 86.6%, respectively. The recycling experiments and the engineering experiments showing that NaClO/BAD can solve the problem of absorption of NO2, and it can be a promising composite absorbent in wet desulfurization and denitrification of marine engine exhaust gas in practical applications. Graphical abstract: Image 1 Highlights: The two-phase wet oxidation absorption system provide a new idea for exhaust gas denitrification. The NaClO/BAD composite absorbent can solve the problem of large amount of NO2 escape by using chlorine-based oxidants. The reaction mechanism of NaClO/BAD composite absorbent for simultaneous removal of SO2 and NOX is proposed. Engineering test was carried out in a local large shipyard in Rongcheng, Shandong.